Counterproductive behaviors and moral disengagement of nurses as potential consequences of stress-related work: validity and reliability of measurement scales - Sili, Alessandro; Fida, Roberta; Zaghini, F.; Tramontano, C.; Paciello, Marinella (La Medicina del Lavoro, 2014)
Background: Several studies, but no one in the nursing, have shown that work stress can facilitate the adoption of specific behaviors that the literature identifies as Counterproductive Work Behaviors (CWB). Individuals, however, not giving up to their moral principles, may transgress social, organizational, moral and ethical norms, through the adoption of moral disengagement (MD). Objectives: The purpose of this study is to validate two specific scales of deviant behaviors and MD in nursing: the Nursing Counterproductive Work Behaviours Scale (Nursing CWBS) and Nursing Moral Disengagement Scale (Nursing MDS). Method: 460 nurses participated in the study. After the adaptation of the Counterproductive Work Behavior Checklist by Spector and Fox to Nursing context (Nursing CWBS) and the ex novo development of the Nursing MDS, the psychometric properties of the two scales were tested. Also, the two scales were correlated. Results: Through a cross-validation approach and based on the results of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), we have shown that the scales have good psychometric properties. Furthermore, the results, attest that the nurse with high levels of MD implements more CWB in the workplace. Conclusions: The Nursing CWBS and Nursing MDS represent a valid starting point for the study of such phenomena in this specific context where stress among nursing staff is sometimes of considerable extent, especially in specific contexts of clinical care.